Pengujian UTAUT Model dalam Pemanfaatan Literasi Informasi Perpustakaan Perguruan Tinggi - Purnomo, Gabriel Wahyu (Jurnal Ilmiah Administrasi Publik, 2019)
Exist an information technology hope to increase use of information literacy. In order for use of information literacy to improve well, the technology used must be able will be accepted and used properly by users. It hope that use of information technology can simplify information literacy activities in college libraries. There are still some differences in the problems that occur in earlier studies about use of information systems, so this study aims to decide how much use of university library information literacy using UTAUT model with descriptive quantitative method. The results of this study show that users are more likely will be interested in utilizing the college library information system for other things than using it for scientific literacy activities. In addition, the moderating effects of age, gender, experience also didn’t have a significant effect. Overall, this model can answer several problems in this study.